Ekstraksi Gelatin Dari Kulit Kelinci Lokal Jawa (Lepus negricollis) Dengan Variasi Jenis Pelarut Dalam Suhu Ekstraksi Serta Aplikasinya Pada Bakso Kelinci - Putri Adek Putro; Mochammad Wachid; Noor Harini (Food Technology and Halal Science Journal, 2019)
Gelatin is a protein obtained from animal collagen tissue found in warts, bones, and connective tissue that is hydrolyzed acidic or basic. The purpose of this study was to determine the different effects of HCl and acetic acid and different extraction temperatures on the production of local rabbit skin gelatin so that the best treatment was obtained in producing gelatin and to determine the effectiveness of local rabbit skin gelatin in rabbit meatball processing. This research was conducted in two stages. The first stage uses a nested random design, namely the extraction of gelatin from the local rabbit skin with different types of acids (HCl 3% and acetic acid 3%) and extraction temperature (50 °C, 60 °C, 70 °C and 80 °C). The parameters observed were yield, moisture content, ash content, protein content, viscosity, pH, and color. The best treatment of Local rabbit skin gelatin based on the SNI approach is in the P1T3 treatment, that treatment soaking with acetic acid and extraction temperature of 70 °C with a yield value of 13.11%, moisture content 5.503%, ash content 1.143%, protein content 63.49%, viscosity 4.466 cP, gel strength 210.532 grams Bloom, and pH 3,967. The second step was making meatballs by comparing the addition of gelatin from local rabbit skin extraction with the best treatment of 3%, commercial gelatin 3%, and without gelatin. The parameters observed included protein content, ash content, moisture content, fat content, texture, and organoleptic. Based on observations of the addition of gelatin in rabbit bakso, increasing the value of protein content, texture, and ash content in bakso while the water and fat content in bakso decreased with the addition of gelatin.